IN-SERVICE TEACHERS’ PERSPECTIVES ON EFL PRE-SERVICE TEACHERS’ PERFORMANCES IN TEACHING YOUNG LEARNERS - Oktarina, Santi (Yavana Bhasha : Journal of English Language Education, 2024)
The present study aimed at investigating the teaching performances of pre-service teachers in teaching English as a Foreign Language (EFL) when instructing young learners, as perceived by in-service teachers. Adopting a descriptive qualitative research design, data were gathered through observations and interviews conducted with 15 students enrolled in the fourth semester of the teaching English as a foreign language subject. The evaluation of the pre-service teachers’ performances was based on an adapted evaluation sheet derived from the government’s professional teacher development program, encompassing criteria related to the commencement, progression, and conclusion of the lesson. Participants were in-service teachers from three distinct educational institutions, selected through purposive sampling. The findings of the study indicated that the pre-service teachers received average scores ranging from 70 to 90 for each criterion, demonstrating their proficiency in teaching young learners. Descriptively, it can be inferred that the pre-service teachers exhibited competent teaching skills within this particular instructional context. Key words: in-service teacher, pre-service teacher, teaching performance, perspective, English for young learner